Analisis Sistem Pengendalian Internal atas Prosedur Pengeluaran Kas Aktivitas Operasional Berbasis COSO Framework 2013 - Muanas, Muanas; Prakoso, Rahadyan Wisnu Jaka (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
In general, operational activities are activities that are the main source of income for a business entity, these operational activities also generate cash flow. Cash flows from operating activities are an important component for the entity, because in these cash flows the entity can evaluate the entity's ability to achieve its objectives. In the cash disbursement process, it is necessary to have a procedure that aims to monitor that the cash issued is in accordance with the entity's objectives, because cash is a financial instrument that can be easily transferred. This study aims to determine the role of internal control in PT. Tw as well as an evaluation of the internal control system for cash disbursements from operational activities at PT. Tw. The data used in this study is primary data with data collection techniques by conducting observations, in-depth interviews and documentation. The author conducted research on the division of Finance & Accounting PT. Tw which is located at JL. Raya Simpang Tiga Jl. Karadenan No.35, Karadenan, Kec. Cibinong, Bogor Regency, West Java 16913. Based on the results of research conducted on procedures, practices and documents used during cash disbursement operational activities, compared to the basic components in the 2013 COSO Framework, namely Control Environment, Risk Assessment, Control Activities, Information & Communication and Monitoring, it can be concluded that the Internal Control System over Operational Activity Cash Disbursement Procedures at PT. Tw has not been fully implemented in accordance with existing theory, the lack of printed SOP documents, the use of internal & external communication that has not been effective and also there is a discrepancy between the operational standards decided by management and practice. Keywords: Internal Control, Cash Disbursement Procedures and COSO Framework 2013